Appearance of pentavalent Fe ion as a result of a charge disproportionation in Fe-substituted Li2MnO3. (March 2021) - Tabuchi, Mitsuharu; Kobayashi, Yasuhiro
Abstract: 20% Fe substituted Li2 MnO3 (Li1+ x (Fe0.2 Mn0.8 )1- x O2, 0 <  x  < 1/3) was prepared using coprecipitation–calcination method. X-ray Rietveld analyses showed that most Fe and Mn ions were on both 4 g and 2 b sites and small amount of them occupy on 2 c and 4 h sites in monoclinic Li2 MnO3 -type structure. Neutron Rietveld analysis revealed that Mn ion was mainly on the 4 g site, whereas Fe ion was on both 4 g and 2 b sites. Temperature dependence of magnetization detected a cusp at 30 K for the sample, originating from its antiferromagnetic nature. The 57 Fe Mössbauer spectrum at 300 K consisted of two symmetric doublets with different isomer shifts. From the isomer shifts, Fe ion existed as 3+ δ and 4+ δ states (0 <  δ  < 1). Below 200 K, the Fe 4+δ component split to two doublets having two isomer shift values assigned as 4+ and 5+ states. At 3 K, the spectrum consisted of magnetically ordered 3+, 4+, and 5+ irons and paramagnetic 4+ state iron. The magnetically ordered pentavalent and tetravalent Fe ions can be stabilized at a highly distorted octahedral 4 g site, whereas magnetically ordered trivalent and paramagnetic tetravalent Fe ions exist mainly on the less distorted octahedral 2 b site. Highlights: 20% Fe-substituted Li2 MnO3 synthesized by coprecipitation – calcination method. The sample is antiferromagnet below 30 K. Above 250 K, 57 Fe Mössbauer spectrum showed that Fe 3+δ and Fe 4+δ components (0 < δ < 1) were coexisted. Below 200 K,   57 Fe Mössbauer spectrum represented that the Fe 4+δ component split to Fe 4+  and Fe 5+  components.